p+33=3

To remove the radical on the left side of the equation, cube both sides of the equation.

p+333=33

Multiply the exponents in ((p+3)13)3.

Apply the power rule and multiply exponents, (am)n=amn.

(p+3)13⋅3=33

Cancel the common factor of 3.

Cancel the common factor.

(p+3)13⋅3=33

Rewrite the expression.

(p+3)1=33

(p+3)1=33

(p+3)1=33

Simplify.

p+3=33

Raise 3 to the power of 3.

p+3=27

p+3=27

Subtract 3 from both sides of the equation.

p=27-3

Subtract 3 from 27.

p=24

p=24

Solve for p cube root of p+3=3